Productive biosensing techniques empowered by all-dielectric metasurfaces - Iwanaga, Masanobu (Frontiers in Bioengineering and Biotechnology, 2025)
Artificially designed, functional nanostructured surfaces, called metasurfaces, are an emerging platform for biosensing. Two major types of metasurface biosensors have been reported: one is based on resonant-wavelength shift and the other is specialized for fluorescence (FL) detection. The all-dielectric metasurfaces that composed of periodic arrays of silicon nanocolumns have a series of optical magnetic-mode resonances, some of which were found to significantly enhance capability for FL detection of diverse target biomolecules, ranging from nucleic acid to antigens and antibodies. Here, we mainly address the recent advances in productive metasurface FL biosensors, provide an overview of the pivotal results, and discuss the future prospects, including artificial-intelligence-driven big data analysis for the next-generation healthcare services.